1997
DOI: 10.1124/mol.52.4.725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein Phosphatase and Kinase Inhibitors on Ca2+and ClCurrents in Guinea Pig Ventricular Myocytes

Abstract: SUMMARYIt is well-established that in heart, both the L-type Ca 2ϩ channel and the cystic fibrosis transmembrane conductance regulator Cl Ϫ channel are regulated by cAMP-dependent phosphorylation. However, it is not clear whether both of these channels are regulated in concert by protein kinase A (PKA) or whether there are mechanisms that independently control the phosphorylation of these two PKA targets. The purpose of this study was to compare the effects of various protein phosphatase and protein kinase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…However, smaller or no effects on basal I Ca were seen in later works that used cell dialysis of inhibitors through the patch pipette or extracellular incubation with cell-permeable inhibitors. The results are divergent, from no effect of Rp-cAMPS (0.1-2 mmol/L in the pipette) and H-89 in adult mouse cardiomyocytes, 92,104,105 through a minor ≈20% reduction in basal I Ca by dialysis of purified PKI protein (2.9 µmol/L) in adult guinea pig myocytes, 88 to 20% to 55% inhibition in late versus early embryonic mouse cardiomyocytes, respectively, after extracellular application of 15 µmol/L of a cell-permeable PKI peptide. 72 Interestingly, reduction in basal I Ca caused by PKA inhibitors 72 or protein phosphatase PP2A 106 was correlated with a decrease in phosphorylation of Ser1928, monitored with a site-specific antibody.…”
Section: Pka Inhibitors and β-Ar Regulationmentioning
confidence: 73%
See 3 more Smart Citations
“…However, smaller or no effects on basal I Ca were seen in later works that used cell dialysis of inhibitors through the patch pipette or extracellular incubation with cell-permeable inhibitors. The results are divergent, from no effect of Rp-cAMPS (0.1-2 mmol/L in the pipette) and H-89 in adult mouse cardiomyocytes, 92,104,105 through a minor ≈20% reduction in basal I Ca by dialysis of purified PKI protein (2.9 µmol/L) in adult guinea pig myocytes, 88 to 20% to 55% inhibition in late versus early embryonic mouse cardiomyocytes, respectively, after extracellular application of 15 µmol/L of a cell-permeable PKI peptide. 72 Interestingly, reduction in basal I Ca caused by PKA inhibitors 72 or protein phosphatase PP2A 106 was correlated with a decrease in phosphorylation of Ser1928, monitored with a site-specific antibody.…”
Section: Pka Inhibitors and β-Ar Regulationmentioning
confidence: 73%
“…Unlike the effect of Iso, the enhancement of basal I Ca by phosphatase inhibitors is not blocked by PKA inhibitors. 92 ; however, a PKC inhibitory peptide was without effect. 92 In all, basal I Ca in mammalian cardiomyocytes is regulated by a balanced action of serine/threonine kinases and phosphatases 104,106,113 ; the kinases involved remain to be identified.…”
Section: Pka Inhibitors and β-Ar Regulationmentioning
confidence: 85%
See 2 more Smart Citations
“…29 Mechanisms other than PDE, such as the enhanced phosphatase activity, can also contribute to the low basal cAMPdependent regulation of I Ca . 30 Indeed, as in other species and myocyte types, [31][32][33] the I Ca of rat atrial myocytes is highly sensitive to phosphatase inhibition; these enzymes appear to play an important role in the basal regulation of the current, keeping with the tight coupling between Ca 2ϩ channels and OA-sensitive phosphatases. 34 Various studies have shown that the kinetics of I Ca inactivation also depend on cAMPdependent regulation of the current 35,36 and the slowly decaying I Ca in HF may be another consequence of its downregulation.…”
Section: Discussionmentioning
confidence: 99%